2006
DOI: 10.1590/s0004-27302006000200024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of obesity

Abstract: This review offers an overview of physiological agents, current therapeutics, as well as medications, which have been extensively used and those agents not currently available or non-classically considered anti-obesity drugs. As obesity - particularly that of central distribution - represents an important triggering factor for insulin resistance, its pharmacological treatment is relevant in the context of metabolic syndrome control. The authors present an extensive review on the criteria for anti-obesity manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 73 publications
0
18
0
6
Order By: Relevance
“…Studies in overweight and obese women with urinary incontinence have shown that a modest (7-8%) weight reduction can improve the frequency of urinary incontinence [11]. Unlike urinary incontinence, the relation between FI and obesity has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in overweight and obese women with urinary incontinence have shown that a modest (7-8%) weight reduction can improve the frequency of urinary incontinence [11]. Unlike urinary incontinence, the relation between FI and obesity has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a modifiable risk factor for FI because obese subjects have higher incidences of pelvic floor dysfunctions [11]. Weight loss in obese women appear to result in improvements in both the frequency and severity of FI episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Essa medicação também possui liberação da Anvisa (Agência Nacional de Vigilância Sanitária), porém nunca foi comercializada no Brasil (32). O topiramato é uma medicação inicialmente liberada para tratamento da epilepsia, que atualmente também é amplamente prescrita para a profilaxia da enxaqueca.…”
Section: Fentermina/topiramatounclassified
“…Furthermore, it is an adjunct to other strategies to treat obese individuals, as it causes weight loss both in laboratory animals and humans (Leombruni et al, 2008;Mancini & Halpern, 2006;Mitchell, Zwaan, & Roerig, 2003). However, the mechanisms underlying the effects of FLX in feeding behavior are affected by factors such as stress and hunger (Hsiao, Chung, Tong, & Cheng, 2006;Gamaro et al, 2008;Placidi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%